The Myth of Sisyphus and the Absurd Hero in The Stranger: A Comparative Analysis of Albert Camus’ Philosophical Principles - Onwanua, Peace; Onwe, Chioma Agatha (Cascades, Journal of the Department of French & International Studies, 2025)
Albert Camus’ The Myth of Sisyphus and The Stranger are widely recognized as foundational texts in the philosophical exploration of absurdism. While previous studies have discussed their existential implications, fewer have examined the dynamic rapport between Camus’ philosophical discourse and its narrative embodiment. This study fills the existing gap in literature by undertaking a comparative analysis of the two works, foregrounding the transformation of abstract philosophical ideas into literary form. It examines how Camus constructs Meursault not merely as a fictional character but as a lived representation of the ―absurd hero, battling through a world stripped of inherent meaning. Adopting a qualitative approach, the research relies on close textual analysis to trace recurring themes such as rebellion, alienation and the pursuit of freedom. By applying existentialist and absurdist theoretical frameworks, it illustrates the consistency between the conceptual argument in The Myth of Sisyphus and its dramatization in The Stranger. In doing so, the study reveals that the novel functions as a philosophical extension indeed, a narrative enactment of Camus’ central tenets concerning man’s confrontation with an indifferent universe. This work contributes to literary and philosophical scholarship by demonstrating how literature serves not only as a reflection of philosophical thought, but also as a powerful mode of its articulation and critique.